Immunomodulatory Effect after Irreversible Electroporation in Patients with Locally Advanced Pancreatic Cancer - He, Chaobin (J Oncol, 2019)
PURPOSE: Irreversible electroporation (IRE) has been demonstrated to be a safe and effective method for locally advanced pancreatic cancer (LAPC). The aim of this study was to evaluate the immunomodulatory effect after IRE and to evaluate the prognostic value of variations of the immune parameters in LAPC patients after IRE. METHODS: Peripheral blood samples of 34 patients were obtained preoperatively and on the third day (D3) and seventh day (D7) after IRE, respectively. The phenotypes of lymphocytes were analyzed by flow cytometry, and dynamic changes of serum levels of cytokines, complement, and immunoglobulin were assayed by enzyme-linked immunosorbent assay. Receiver operating characteristic (ROC) curve and concordance index (C-index) were used to compare the survival predictive ability. RESULTS: There was a transitory decrease followed by a steady increase for CD4(+) T cell, CD8(+) T cell, NK cell, IL-2, C3, C4, and IgG while a reverse trend was detected for Treg cell, IL-6, and IL10 after IRE. The alteration of CD8(+) T cell between D3 and D7 was identified as a prognostic factor for both overall survival (OS) and progression-free survival (PFS). The values of ROC curve (AUC) and C-indexes of the alteration of CD8(+) T cell for OS and PFS were 0.816 and 0.773 and 0.816 and 0.639, respectively, which were larger than those of other immune or inflammation-based indexes. CONCLUSIONS: This study presented the first evidence of IRE-based immunomodulatory in patients with LAPC. The alteration of CD8(+) T cell between D3 and D7 showed relatively good performance and could be used as an effective tool for prognostic evaluation for LAPC patients after IRE.